Use Of Statins Among Patients From African Ethnic Minority Backgrounds With T2DM. The Evidence In Relation To Treatment Efficacy And Adherence: A Systematic Review - Yensi, Gladys (2012)
Introduction: Diabetes is a generic term for a group of disorders which share a number of common features. This systematic review investigates a variety of issues related to the use of statin medication in real-life environments among patients from black African ethnic backgrounds, especially those with T2DM. The review summarises the importance of Type 2 diabetes as a condition, the importance of cardiovascular disease as a significant co-morbidity associated with diabetes, especially among black African patients, and the role of statin medication as a pharmacological intervention to reduce this cardiovascular risk. Aims: To systematically review to what extent does the research evidence in relation to levels of adherence to statin therapy among patients from black African ethnic backgrounds with T2DM, support the use of statins as an effective form of therapy. Method: A stringent search strategy of electronic literature search was carried out according to the inclusion and exclusion criteria then devises a systematic approach to identifying literature using quality assessment tool Result: Of the two hundred and forty-four potentially identified relevant studies, fourteen were included in the studies for analysis. Three key themes apparent from the findings were 1) prescription of statins for black patients; 2) adherence to statins by black patients; 3) efficacy of statins for black patients. Conclusion: From this review it can be concluded that both adherence and statin prescription levels are significantly reduced in black patients compared to their white counterparts but that the reasons for this disparity are poorly understood. In addition the review identifies that the level of understanding in relation to the effectiveness of specific statin medication regimes in this particular patient group, even once the above disparities are controlled for, is underdeveloped.